2013
DOI: 10.1007/s10096-013-1983-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term dissemination of acquired AmpC β-lactamases among Klebsiella spp. and Escherichia coli in Portuguese clinical settings

Abstract: We investigated the occurrence, diversity and molecular epidemiology of genes coding for acquired AmpC β-lactamases (qAmpC) among clinical isolates of Enterobacteriaceae lacking inducible chromosomal AmpCs in Portugal. A total of 675 isolates non-susceptible to broadspectrum cephalosporins obtained from four hospitals and three community laboratories during a 7-year period (2002)(2003)(2004)(2005)(2006)(2007)(2008) were analysed. The presence of genes coding for qAmpC was investigated by phenotypic criteria, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 51 publications
5
19
0
Order By: Relevance
“…Results are in agreement with previous studies that demonstrated a wide dissemination of resistance to these antibiotics among E. coli isolates from Portuguese clinical settings (Freitas et al, 2014), animals (Radhouani et al, 2009) and aquatic systems (Pereira et al, 2013). For antibiotics mainly used in human medicine such as 3rd generation cephalosporins, ciprofloxacin and imipenem, levels of resistance were low.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Results are in agreement with previous studies that demonstrated a wide dissemination of resistance to these antibiotics among E. coli isolates from Portuguese clinical settings (Freitas et al, 2014), animals (Radhouani et al, 2009) and aquatic systems (Pereira et al, 2013). For antibiotics mainly used in human medicine such as 3rd generation cephalosporins, ciprofloxacin and imipenem, levels of resistance were low.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, it is a matter of concern that levels of resistance to 3rd generation cephalosporins have been consistently increasing in isolates from clinical settings in Portugal (ECDC, 2013). For example, gene bla CMY−2 , which was here detected in one isolate from seagull feces, has been detected in E. coli from clinical samples in Portuguese health care settings (Freitas et al, 2014). …”
Section: Discussionmentioning
confidence: 83%
“…To be more specific, the majority of Acinetobacter baumannii isolates were producers of carbapenemase and metallo-β-lactamase (12). In a study of isolates collected between 2002 and 2008, DHA-1 was the most prevalent acquired AmpC (94%), which was first identified in 2003 and was detected throughout the studied period in different institutions (13). Klebsiella pneumoniae is an important cause of nosocomial infection, and ESBLs and carbapenemases are a cause of emergency in multidrug-resistant (MDR) Klebsiella pneumoniae treatment (14).…”
Section: Introductionmentioning
confidence: 99%
“…They were recovered during a 4-year period (2010-2013) from general hospitals located at the North (HA; 63.2%; 2010-2012) and Centre (HD; 5.5%; June 2012-August 2013) of Portugal, and a community laboratory at the North (CL2; 31.4%; August 2012-August 2013), all serving a population of almost 3 000 000 people. Bacterial identification and antibiotic susceptibility testing were performed as described [8] .…”
Section: Methodsmentioning
confidence: 99%
“…Our previous survey on qAmpC-producing Enterobacteriaceae dates back to the period of 2002 to 2008, and indicated a high occurrence of DHA-1-producing K. pneumoniae isolates [8] , but detailed molecular analysis was not performed and more recent epidemiological trends are not known. We aim to provide detailed molecular data on clinical qAmpC producing Enterobacteriaceae from two different periods (2002-2008 and 2010-2013) in order to clarify the contribution of clonal and plasmid genetic platforms for the current epidemiological scenario concerning extended-spectrum beta-lactams resistance.…”
Section: Introductionmentioning
confidence: 99%